2009
DOI: 10.1002/joc.1930
|View full text |Cite
|
Sign up to set email alerts
|

Regional variation in perceptions about climate change

Abstract: A 2007 survey covering rural areas in nine US states provides data on perceived local impacts of climate change. Perceptions vary from region to region, with a pattern suggesting links to real climate -specifically to winter warming in snow country. A multivariate analysis using mixed-effects ordered logit regression confirms a significant perception-temperature relationship, net of individual background and ideological characteristics, and of regional variations. These findings invite more detailed research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
180
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(201 citation statements)
references
References 22 publications
14
180
1
3
Order By: Relevance
“…Consistent with previous work (see Leiserowitz 2006;Semenza et al 2008), we observed that people with higher levels of education perceive a lower risk associated with climate change. Our finding on spatial (regional, rural-urban) differentials in perceived climate change is also supported in the extant literature (see Thomas et al 2007;Hamilton and Keim 2009;Sanchez et al 2012). The significance of coping capacity in terms of self-rated ability to handle work pressure and responsibilities as well as self-rated ability to handle personal pressure and unexpected difficulties suggest the importance and complexity of the two psychosocial factors in shaping perception of climate change.…”
Section: Multinomial Logistic Regressionsupporting
confidence: 85%
“…Consistent with previous work (see Leiserowitz 2006;Semenza et al 2008), we observed that people with higher levels of education perceive a lower risk associated with climate change. Our finding on spatial (regional, rural-urban) differentials in perceived climate change is also supported in the extant literature (see Thomas et al 2007;Hamilton and Keim 2009;Sanchez et al 2012). The significance of coping capacity in terms of self-rated ability to handle work pressure and responsibilities as well as self-rated ability to handle personal pressure and unexpected difficulties suggest the importance and complexity of the two psychosocial factors in shaping perception of climate change.…”
Section: Multinomial Logistic Regressionsupporting
confidence: 85%
“…Recent studies, however, find evidence that people's personal experience of natural hazards or climate change 2 are related to their attitude on climate change and climate policy (e.g., Akerlofa et al 2013;Donner and McDaniels 2013;Hamilton and Keim 2009;Howe et al 2013;Leiserowitz 2006;Myers et al 2013;Spence et al 2011Spence et al , 2012Weber 2010). Spence et al (2011), for example, find that those who have experienced flooding express more concern over climate change and that this translates into a 1 There is some evidence for risk denial when facing natural hazards.…”
Section: Natural Hazards Climate Change and Perceptionsmentioning
confidence: 99%
“…The relationships between exposure to extreme weather events and the way people feel about climate change and possible response strategies becomes more consistent when an additional factor is taken into account: namely, how individuals interpret such "climate signals" 27,39 . People who report having experienced changes or events in the natural environment that they think were caused by climate change are more likely to believe that climate change is relevant to their local area and themselves 42 than people who did not report such experience.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, one study found that Britons who had recently experienced flooding (a weatherrelated phenomenon expected to occur more frequently in Britain because of climate change) perceived their local area to be more at risk from climate change, were more concerned about climate change impacts, had higher confidence in their ability to mitigate climate change, and were more willing to reduce their energy use in order to mitigate climate change than those who had not recently experienced flooding 26 . While some studies have revealed similar patterns 34-36 , other work suggests that experiencing the impacts of extreme weather events does not necessarily increase concern and the willingness to respond to climate change 37,38 .The relationships between exposure to extreme weather events and the way people feel about climate change and possible response strategies becomes more consistent when an additional factor is taken into account: namely, how individuals interpret such "climate signals" 27,39 . People who report having experienced changes or events in the natural environment that they think were caused by climate change are more likely to believe that climate change is relevant to their local area and themselves 42 than people who did not report such experience.…”
mentioning
confidence: 98%